Think twice: how single-cell suspensions from solid tissues for single-cell transcriptomics are well prepared - Meng-Meng Qu; Yan-Mei Jiao; Haijuan Wang (​​​​​​​​Infectious Diseases & Immunity)
Abstract. Due to its technological advantages, single-cell sequencing has become an increasingly utilized tool to unravel the heterogeneity and complexity of individuals. The preparation of a high-quality single-cell suspension from solid tissues is a critical step prior to single-cell RNA sequencing. Based on a brief overview of the steps involved in preparing cell suspensions from solid tissues for single-cell RNA sequencing, we present a detailed analysis of the pivotal steps in the preparation process, including enzymatic digestion, mechanical dissociation, and cell viability evaluation. The clarification of these experimental details will greatly help us obtain high-quality single-cell sequencing data from solid tissues.